Detailed Description
The following is a preferred embodiment of the present application, and it should be noted that, for those skilled in the art, various modifications and embellishments can be made without departing from the principle of the present application, and these modifications and embellishments are also regarded as the scope of the present application.
The following disclosure provides many different embodiments or examples for implementing different features of the application. In order to simplify the disclosure of the present application, specific example components and arrangements are described below. Of course, they are merely examples and are not intended to limit the present application. Moreover, the present application may repeat reference numerals and/or letters in the various examples, such repetition is for the purpose of simplicity and clarity and does not in itself dictate a relationship between the various embodiments and/or configurations discussed. In addition, the present application provides examples of various specific processes and materials, but one of ordinary skill in the art may recognize applications of other processes and/or use of other materials.
Referring to fig. 1, a flow chart of a method for manufacturing a housing according to an embodiment of the present disclosure includes:
s101: coating and/or soaking a polymer ceramic blank with pretreatment liquid, and drying to form a pretreatment layer on the surface of the polymer ceramic blank to obtain a composite blank, wherein the polymer ceramic blank comprises a polymer, and the pretreatment liquid comprises an accelerator capable of accelerating polymer crosslinking.
S102: and after the composite blank is subjected to heat treatment and hot pressing, removing the pretreatment layer to obtain a polymer ceramic layer, and thus obtaining the shell.
In the application, after the polymer ceramic body is treated by the pretreatment liquid, the accelerator in the pretreatment liquid can promote the crosslinking of the polymer in the polymer ceramic body in the heat treatment process, and meanwhile, the heat treatment time is greatly reduced, so that the mechanical property of the prepared shell 100 can be improved, the preparation time is greatly shortened, and the preparation efficiency is improved. In the related art, various materials such as glass, metal, plastic, and ceramic can be used in the electronic device 200, but the glass has high dielectric loss, has a certain limitation in millimeter wave use, and the anti-drop performance of the glass needs to be improved; the metal can shield the product signal due to the conduction; the texture of the plastic needs to be improved; the high dielectric constant of the ceramic can cause signal damage to a great extent. In the present application, by providing the polymer ceramic layer 10, the high-grade texture of the ceramic is maintained, and the dielectric properties meet the requirements of millimeter waves so as to meet the requirements of 5G communication technology. Meanwhile, the inventor of the present application finds that the polymer ceramic layer 10 has low surface hardness, poor scratch resistance, insufficient product strength, incapability of realizing thin thickness, long overall processing time and low production efficiency; therefore, the inventor of the present application coats and/or soaks the polymer ceramic body with the pretreatment liquid, so that in the heat treatment process, the accelerator in the pretreatment liquid can promote the crosslinking of the polymer in the polymer ceramic body, and improve the crosslinking degree of the polymer, so that the heat treatment duration can be greatly reduced, the production efficiency can be improved, the hardness of the shell 100 can be improved, the scratch resistance can be improved, and the application of the shell can be facilitated.
In S101, a composite body is obtained by coating and/or soaking the polymer ceramic body with a pretreatment liquid, drying and then forming a pretreatment layer on the surface of the polymer ceramic body. Through pretreatment, a pretreatment layer is formed on the surface of the polymer ceramic body, the polymer ceramic body comprises a polymer, and the pretreatment layer is provided with an accelerant capable of promoting the crosslinking of the polymer, so that the crosslinking of the polymer can be promoted in the subsequent heat treatment process, and the crosslinking degree is improved.
Referring to fig. 2, a flow chart of a method for preparing a polymer ceramic body according to an embodiment of the present application is provided, which includes:
s1011: and mixing the ceramic particles and the polymer, and granulating to obtain the injection molding feed.
S1012: and injection molding the feed to obtain a polymer ceramic blank.
In S1011, the injection molding feed is formed by mixing and granulating the ceramic particles and the polymer, which is beneficial to the subsequent injection molding.
In an embodiment of the present application, the ceramic particles include at least one of zinc oxide, zirconium oxide, aluminum oxide, silicon dioxide, titanium oxide, and silicon carbide. The ceramic particles are high temperature resistant, corrosion resistant, high in hardness and good in strength, and are beneficial to improving the performance of the shell 100. In an embodiment, the refractive index of the ceramic particles is greater than 2, which is favorable for further improving the ceramic texture of the casing 100. In the present embodiment, the ceramic particles have a diameter of 20nm to 1 μm. The selection of the above-mentioned size of the ceramic particles facilitates mixing with the polymer and also facilitates increasing the ceramic phase content of the shell 100. Further, the diameter of the ceramic particles is 100nm to 800nm. Further, the ceramic particles have a diameter of 300nm to 600nm. Specifically, the diameter of the ceramic particles may be, but not limited to, 50nm, 100nm, 250nm, 400nm, 500nm, 650nm, 700nm, 800nm, 900nm, 1 μm, or the like. It is understood that the morphology of the ceramic particles may be, but is not limited to, spherical, spheroidal, etc.
In the present application, by mixing the ceramic particles with the polymer, it is advantageous to reduce the quality of the case 100 while improving the toughness of the case 100. In an embodiment of the present application, the polymer comprises a thermoplastic resin comprising at least one of polyphenylene sulfide, polyphenylene sulfone, polyamide, and ethylene vinyl acetate. The physical and chemical properties of the thermopolymer can be matched with the preparation process of the shell 100, decomposition cannot occur in the preparation process, the difficulty of the preparation process cannot be increased, and the production cost can be reduced.
It is understood that, when the ceramic particles and the polymer are mixed, the mixing ratio of the ceramic particles and the polymer may be selected according to the content of each substance in the polymer ceramic layer 10, and is not limited thereto. In one embodiment, the mass ratio of ceramic particles to polymer is (0.5-0.8): (0.2-0.5) is favorable for preparing the polymer ceramic layer 10 with high hardness, good strength and strong ceramic texture. In one embodiment, 50% -80% by mass of the ceramic particles are mixed with 20% -50% of the polymer to form a mixture.
In embodiments herein, mixing comprises at least one of blending and banburying. Specifically, mixing may be performed in at least one of a blending extruder and an internal mixer to uniformly disperse the respective substances in the mixture. In one embodiment, the mixture is blended and/or banned 2-5 times, with the duration of one blend or banburying being 1h-2h. Specifically, the temperature for blending or banburying is 300-350 ℃. In the application, the injection molding feed can be obtained by granulating the mixed material. In one embodiment, the ceramic particles and the polymer may be mixed and then placed in an internal mixing and granulating machine, and the injection molding feed is obtained after internal mixing and granulating. Specifically, the temperature of banburying granulation can be but is not limited to 200 ℃ to 350 ℃, and the time of banburying granulation can be but is not limited to 1h to 12h. Furthermore, the banburying process is in a negative pressure state, and the absolute value of the pressure is less than 0.01MPa, so that the polymer is effectively prevented from being oxidized, and the elimination of gas generated by side reaction can be effectively promoted.
In S1012, the injection molding process parameters may be selected according to the properties of the selected polymer. In an embodiment of the application, the method further comprises drying the injection molding feed before injection molding. In one embodiment, the drying treatment comprises drying at 90-150 ℃ for 8-12 h. The water in the injection molding feed is removed through a drying process. In one embodiment of the present application, when the polymer comprises at least one of polyphenylene sulfide, polyphenylene sulfone, polyamide and ethylene-vinyl acetate copolymer, the injection molding temperature is 320 ℃ to 360 ℃, the injection speed is 70% to 100%, and the injection pressure is 120MPa to 250MPa; the temperature of the die is 130-180 ℃, and the pressure maintaining time is 2-60 s, so as to obtain the polymer ceramic blank. Further, the molding temperature of the injection molding is 320-340 ℃, the injection speed is 70-90%, and the injection pressure is 150-200 MPa; the temperature of the die is 140-170 ℃, and the pressure maintaining time is 5-50 s, so as to obtain the polymer ceramic blank. The polymer ceramic blank with good molding effect and high molding yield can be obtained by adopting the conditions for injection molding. The shape of the polymer ceramic body obtained by injection molding can be selected according to the requirement, and the thickness of the polymer ceramic body can also be selected according to the requirement. It is understood that other forming methods such as tape casting and the like can be adopted to prepare the polymer ceramic body. In the application, the injection molding method is simpler to operate, the compatibility problem between a solvent and a polymer phase does not need to be considered in comparison with tape casting, and the preparation cost is low.
Referring to fig. 3, a flow chart of a method for manufacturing a polymer ceramic green body according to another embodiment of the present application is provided, which includes:
s2010: and (4) pretreating the ceramic particles to obtain the treated ceramic particles.
S2011: and mixing the treated ceramic particles with a polymer, and granulating to obtain the injection molding feed.
S2012: and injection molding the feed to obtain a polymer ceramic blank.
In S1011, the injection molding feed is formed by mixing and granulating the ceramic particles and the polymer, which is beneficial to the subsequent injection molding.
It is to be understood that the detailed descriptions of S2011 and S2012 refer to the descriptions of the corresponding parts of S1011 and S1012 in the above embodiments, and are not repeated herein.
In one embodiment of the present application, the pre-treating the ceramic particles to obtain treated ceramic particles comprises: and carrying out modification treatment on the ceramic particles, and carrying out spray granulation to obtain the treated ceramic particles. By modifying the ceramic particles, the compatibility of the ceramic particles with the polymer is improved, thereby improving the performance of the housing 100.
In one embodiment of the present application, the ceramic particles are modified by mixing the ceramic particles with a modifying agent. Optionally, the modifier comprises at least one of a silane coupling agent, ammonium citrate, polyacrylic acid, ammonium polymethacrylate, and triethanolammonium. In the present application, the modifier may be selected according to the properties of the polymer. In another embodiment of the present application, when the ceramic particles are mixed with the modifier, the ceramic particles are 60 to 98 parts by weight and the modifier is 0.1 to 3 parts by weight. The mixing ratio can be such that the ceramic particles are completely modified and the modifier is not agglomerated. Furthermore, when the ceramic particles and the modifier are mixed, the weight portions of the ceramic particles are 60 to 80 portions, and the weight portions of the modifier are 0.5 to 2 portions. In another embodiment of the present application, a dispersing aid is further added when the ceramic particles are mixed with the modifier, so that the ceramic particles are better uniformly dispersed. Specifically, the ceramic particles are 60 to 98 parts by weight, the modifier is 0.1 to 3 parts by weight, and the dispersing aid is 0.1 to 1 part by weight when the ceramic particles are mixed. In yet another embodiment of the present application, a colorant is added to the ceramic particles when they are mixed with the modifier, so that the apparent color of the polymer ceramic body can be improved. Specifically, the ceramic particles are 60 to 98 parts by weight, the modifier is 0.1 to 3 parts by weight, and the colorant is 1 to 20 parts by weight when the ceramic particles and the modifier are mixed. In the present application, the colorant includes at least one of an organic colorant and an inorganic colorant, and the colorant may be selected according to a desired color, for example, the colorant may be selected from cobalt oxide or carbon black, etc., to make the polymer ceramic body black, and the colorant may be, but not limited to, at least one selected from iron oxide, cerium oxide, nickel oxide, bismuth oxide, zinc oxide, manganese oxide, chromium oxide, copper oxide, vanadium oxide, and tin oxide, etc. In another embodiment of the present application, when the ceramic particles are mixed with the modifier, a dispersant and a colorant are further added, wherein the ceramic particles are 60 to 98 parts, the modifier is 0.1 to 3 parts, the dispersing aid is 0.1 to 1 part, and the colorant is 1 to 20 parts.
In another embodiment of the present application, the ceramic particles are mixed with the modifier to obtain a mixed material, and the mixed material is ball-milled to obtain a mixed slurry. It will be appreciated that when a dispersant and/or a colorant is added, a mixed material is obtained after all the substances are mixed, and the mixed material is then ball milled. Optionally, the ball milling comprises mixing the mixed material, water and ball milling beads, and ball milling for 12h-48h to completely modify the ceramic particles. In one embodiment, the mass ratio of the mixed material, water and ball milling beads is 1: (1-3): (0.5-1), which is beneficial to the full mixing of the mixed materials and the modification of the ceramic particles. Specifically, the mass ratio of the mixed material, water and ball milling beads can be, but is not limited to, 1. In the present application, the ball milling may be carried out at room temperature, e.g., 15 ℃ to 35 ℃, etc.
In yet another embodiment of the present application, the slurry is mixed to obtain treated ceramic particles after spray granulation. Specifically, the temperature of spray granulation may be selected according to the temperature of the solvent in the mixed slurry, and spray granulation may be performed in a spray granulator. In one embodiment, the feeding temperature is 70-80 ℃, the air inlet temperature is 130-160 ℃, the air outlet temperature is 70-85 ℃, the temperature in the tower is 70-90 ℃ and the negative pressure in the tower is 50-150 pa in the spray granulation process. Through the process, the treated ceramic particles with uniform sizes can be formed, and the mixing between the ceramic particles and the polymer is facilitated. Specifically, after spray granulation, the diameter of the treated ceramic particles is 100nm-1 μm.
In an embodiment of the present application, a polymer ceramic body includes a polymer and ceramic particles. Further, the ceramic particles are uniformly dispersed in the polymer ceramic body.
In S101, the pretreatment liquid includes an accelerator capable of accelerating crosslinking of the polymer. In embodiments herein, the accelerator comprises at least one of an organic accelerator and a metallic accelerator to promote crosslinking of the polymer. In one embodiment, the organic accelerator includes at least one of amines, phenols, benzenes, and ethers. Specifically, the organic accelerator includes at least one of melamine, hexamethoxymethyl melamine, trihydroxybenzene, pentaerythritol triallyl ether, phenol, and hindered phenols. In another embodiment, the metal promoter includes at least one of silver, copper, iron, lead, zinc, and magnesium. In the present application, the pretreatment liquid may contain only an organic accelerator, and may contain only a metal accelerator; it is also possible to include both organic and metallic promoters. The inventor of the application discovers that the crosslinking speed can be further increased by adding the organic promoter and the metal promoter at the same time, a higher crosslinking level can be achieved in the same time, the processing time is further reduced, and the preparation time is shortened. In one embodiment, the mass ratio of the organic promoter to the metal promoter in the accelerator is 1.2 to 4, thereby facilitating rapid increase in the degree of crosslinking of the polymer in subsequent heat treatment. Further, the mass ratio of the organic promoter to the metal promoter in the promoter is 1.5-3.5. Specifically, the mass ratio of the organic promoter to the metal promoter in the promoter may be, but is not limited to, 1.5, 2, 2.5, 2.8, 3, 3.4, 3.5, or the like. In a specific embodiment, melamine and zinc may be mixed in a mass ratio of 1.2 to 4 as an accelerator. In another embodiment of the present application, the accelerator is present in the pretreatment in an amount of 10 to 50% by mass. The accelerator with the content can effectively promote the crosslinking of the polymer in the subsequent treatment process, and can be well dispersed in the pretreatment liquid. Further, the mass content of the accelerator in the pretreatment is 15-45%. Furthermore, the mass content of the accelerator in the pretreatment is 20-40%. Specifically, the mass content of the accelerator in the pretreatment may be, but not limited to, 15%, 18%, 22%, 25%, 27%, 30%, 35%, 40%, 43%, or the like.
In one embodiment of the present application, the pretreatment liquid includes a solvent. In one embodiment, the mass content of the solvent in the pretreatment liquid is 50% to 80%. Further, the mass content of the solvent in the pretreatment liquid is 60-80%. Furthermore, the mass content of the solvent in the pretreatment liquid is 65-75%. Specifically, the mass content of the solvent in the pretreatment may be, but not limited to, 52%, 55%, 57%, 60%, 63%, 65%, 70%, 76%, 79%, or the like. In the present application, the solvent includes at least one of water, ethanol, and acetone. In another embodiment of the present application, the pretreatment liquid includes a dispersant. The uniform dispersion degree of the accelerator is improved by adding the dispersant. In one embodiment, the mass content of the dispersant in the pretreatment liquid is 0.5% to 5%. Further, the mass content of the dispersing agent in the pretreatment liquid is 1-3.5%. Specifically, the mass content of the dispersant in the pretreatment may be, but not limited to, 0.5%, 1%, 1.8%, 2%, 2.5%, 3%, 3.7%, 4%, 4.5%, or the like. In another embodiment, the dispersant includes at least one of a silane coupling agent, stearic acid, ammonium stearate, and polyethylene glycol. In another embodiment of the present application, the pretreatment liquid includes a binder. The accelerant is attached to the surface of the polymer ceramic body after spraying and soaking by adding the binder. In one embodiment, the mass content of the binder in the pretreatment liquid is 1% to 5%. Furthermore, the mass content of the binder in the pretreatment liquid is 1.5-4%. Furthermore, the mass content of the binder in the pretreatment liquid is 2-3.5%. Specifically, the mass content of the binder in the pretreatment may be, but not limited to, 1%, 1.8%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 4.7%, or the like. In another embodiment, the binder comprises at least one of polyvinyl alcohol, polyvinyl butyral, polyethylene glycol, and acrylic resin. In one embodiment, the pretreatment liquid includes an accelerator, a dispersant, a binder, and a solvent. Furthermore, the mass content of the accelerator in the pretreatment liquid is 10-50%, the mass content of the dispersant is 0.5-5%, the mass content of the binder is 1-5%, and the mass content of the solvent is 50-80%, so that the uniform dispersion of the accelerator can be ensured, and the accelerator can be attached to the surface of the polymer ceramic blank after the polymer ceramic blank is treated.
In the application, the pretreatment liquid may be coated on the surface of the polymer ceramic body by a coating method, or the polymer ceramic body may be immersed in the pretreatment liquid, so that a pretreatment layer may be formed on the surface of the polymer ceramic body after drying. In the embodiment of the application, the coating and/or soaking comprises treatment for 1-2 h at 15-40 ℃ so that the pretreatment liquid can be uniformly attached to the polymer ceramic blank. Further, the coating and/or soaking comprises treating at 20-35 ℃ for 1-2 h. In an embodiment of the application, the drying comprises a treatment at 80 ℃ to 100 ℃. Further, the drying includes treatment at 85 ℃ to 100 ℃. Specifically, the drying time can be selected according to the volatilization condition of the solvent.
In the embodiment of the present application, the thickness of the pretreatment layer is 10 μm to 100. Mu.m. Specifically, the thickness of the pretreatment layer may be, but not limited to, 10 μm, 20 μm, 40 μm, 50 μm, 70 μm, 85 μm, 100 μm, or the like. The pretreatment layer with the thickness can promote the crosslinking of the polymer in the subsequent heat treatment process, and meanwhile, the waste is avoided. The composite body is a polymer ceramic body and a pretreatment layer arranged on the surface of the polymer ceramic body. It is understood that the pretreatment layer can be disposed on one or more surfaces of the polymer ceramic body, or on all surfaces of the polymer ceramic body, and can be selected as desired.
In S102, crosslinking the polymer in the polymer ceramic blank through heat treatment, and accelerating the crosslinking degree of the polymer and reducing the heat treatment time under the action of an accelerator; and internal pores are eliminated after hot pressing, so that the density is improved; further, the pre-treatment layer is removed to obtain the polymer ceramic layer 10, and the housing 100 is manufactured.
In an embodiment of the present application, the time of the heat treatment is less than or equal to 12h. Further, the time of the heat treatment is less than or equal to 8 hours. Further, the time of the heat treatment is less than or equal to 5 hours. In the related technology, the crosslinking degree of the polymer is improved through heat treatment, the heat treatment time is 48-72 h, the preparation time is greatly prolonged, and the production efficiency is reduced. The inventor of the application discovers that the accelerator reacts with the polymer in the heat treatment process by arranging the pretreatment layer on the surface of the polymer ceramic blank, so that the crosslinking of the polymer is further promoted on the basis of the original crosslinking of the polymer, and the integral crosslinking degree is improved; compared with a polymer ceramic blank which is not treated by the pretreatment liquid, the polymer ceramic layer 10 prepared from the composite blank has the advantages of higher crosslinking degree of the polymer, high surface hardness, good scratch resistance effect and good overall strength, and meanwhile, the heat treatment time is greatly shortened and is less than or equal to 12 hours.
In one embodiment of the present application, the temperature of the heat treatment is greater than the melting temperature of the polymer and less than the decomposition temperature of the polymer. In another embodiment of the application, the heat treatment comprises raising the temperature from 15 ℃ to 40 ℃ to 220 ℃ to 280 ℃ within 0.5h to 1h, then preserving the heat for 0.5h to 2h, raising the temperature from 220 ℃ to 280 ℃ to 300 ℃ to 380 ℃ within 0.5h to 1h, and then preserving the heat for 0.5h to 4h. By adopting the segmented heat treatment process, the composite body can be heated uniformly, and the crosslinking degree of the polymer is uniform. In the first stage, the polymer in the polymer ceramic blank is pre-softened, and the accelerator in the pre-treatment layer can permeate into the polymer ceramic blank to react with the polymer; in the second stage, the temperature is increased and further cross-linking between the polymers occurs, thereby increasing the surface hardness and overall strength of the housing 100. In one embodiment, when the polymer ceramic bodies are subjected to heat treatment, the heat treatment comprises raising the temperature from 15 ℃ to 40 ℃ to 220 ℃ to 280 ℃ within 0.5h to 1h, then preserving the heat for 24h, raising the temperature from 220 ℃ to 280 ℃ to 300 ℃ to 380 ℃ within 0.5h to 1h, and then preserving the heat for 24h, wherein the heat treatment time is far longer than the heat treatment time. In one embodiment, when the polymer comprises at least one of polyphenylene sulfide, polyphenylene sulfone, polyamide and ethylene-vinyl acetate copolymer, the heat treatment process described above can be employed, greatly reducing the heat treatment duration and increasing the degree of crosslinking of the polymer.
In this application, through the inside compactness of hot pressing promotion, reduced inside micro defect, improved the intensity of casing 100. In embodiments of the present application, the temperature of the hot pressing is greater than the glass transition temperature of the polymer and less than the decomposition temperature of the polymer. Further, the hot pressing temperature is 20 ℃ to 60 ℃ higher than the glass transition temperature of the polymer. Within this range, the polymer is in a high elastic state, and the molecular chains can move to make the space between the polymer and the ceramic particles more compact under the action of pressure, thereby improving the performance of the shell 100. In one embodiment of the application, the hot pressing comprises treating at 300 ℃ -400 ℃ for 2h-12h at 20MPa-80 MPa. By adopting the hot pressing process, the compactness degree in the polymer ceramic layer 10 can be enhanced, and the strength of the shell 100 is further improved. Further, the hot pressing comprises the step of treating for 3 to 10 hours at the temperature of between 310 and 460 ℃ and under the pressure of between 30 and 70 MPa. Specifically, the pressure of hot pressing can be, but is not limited to, 28MPa, 35MPa, 40MPa, 45MPa, 50MPa, 60MPa, 75MPa, etc., the temperature of hot pressing can be, but is not limited to, 310 ℃, 320 ℃, 340 ℃, 350 ℃, 360 ℃ or 380 ℃, etc., and the time of hot pressing can be, but is not limited to, 2h, 4h, 5h, 7h, 10h, 11h, etc. In another embodiment of the present application, when the polymer includes at least one of polyphenylene sulfide, polyphenylene sulfone, polyamide, and ethylene-vinyl acetate copolymer, the hot pressing process described above may be employed. Specifically, the hot pressing may be performed in, but not limited to, a hot pressing sintering furnace, and the whole process is performed under an inert atmosphere, such as nitrogen or argon may be introduced. In the present application, after hot pressing, the polymer ceramic layer 10 can be removed after natural cooling.
In the present application, the polymer ceramic layer 10 having high surface hardness and high strength can be obtained by removing the pretreatment layer after hot pressing. In the embodiment of the present application, the pre-treatment layer is removed by at least one of computer numerically controlled precision machining (CNC machining) and lapping and polishing. The pre-treatment layer can be removed by CNC processing and the final desired assembled fit of the polymeric ceramic layer 10 is obtained; the polymeric ceramic layer 10 is made more flat, for example by CNC machining. The process conditions of the CNC machining can be selected as required. In a specific embodiment, the polymer ceramic body after hot pressing is subjected to CNC machining according to a required shape, wherein the CNC machining is performed by a polycrystalline diamond (PCD) milling cutter, the rotating speed of a main shaft is 10000-25000 rpm, and the single cutting amount is 10-500 mu m. By grinding and polishing, not only the pretreatment layer can be removed, but also the roughness of the surface of the polymer ceramic layer 10 can be reduced. In the application, a five-axis grinding and polishing machine, a 13.6B double-face grinding machine or a sweeping machine and the like can be selected for processing. In one embodiment, the lapping polishing includes rough polishing and fine polishing. Specifically, the rough polishing can be at least one of a sweeping machine, a double-sided grinder and a five-axis polisher, the polishing disc is selected from one or more of pig hair, a buffing disc, damping cloth, glue silk, copper wire, a carpet or a composite material of pig hair and buffing, the rough polishing liquid comprises at least one of water-system diamond polishing liquid and oil-system diamond polishing liquid, the granularity of diamond micro powder in the rough polishing liquid is 0.5-20 mu m, and the concentration of the rough polishing liquid is 1-30 wt%; the fine polishing can be at least one of a sweeping machine and a double-sided grinder, the fine polishing liquid comprises at least one of silicon oxide polishing liquid and cerium oxide polishing liquid, the particle size of particles in the fine polishing liquid is 50-500 nm, and the concentration of the fine polishing liquid is 5-45 wt%. In one embodiment, the CNC machining may be performed first, and then the grinding and polishing may be performed, so that the pre-treatment layer may be effectively removed, and the smooth surface of the polymer ceramic layer 10 may be obtained.
In the embodiment of the present application, the method for manufacturing the housing 100 further includes spraying or depositing a protective material on the surface of the polymer ceramic layer 10 to form the protective layer 20; specifically, the thickness of the protective layer 20 may be, but is not limited to, 0.5 μm to 3 μm, and the deposition may be, but is not limited to, evaporation coating, sputtering, vacuum plating, and the like. In one embodiment, the anti-fingerprint layer is formed by coating the anti-fingerprint agent on the surface of the polymer ceramic layer 10, so as to enhance the anti-fingerprint effect of the casing 100. In another embodiment, the hardened layer is formed by evaporating a hardening material on the surface of the polymer ceramic layer 10. Specifically, the hardened material may include, but is not limited to, at least one of graphite, alumina, zirconia, silica, chromium nitride, and titanium nitride.
The present application further provides a housing 100, which is manufactured by the manufacturing method according to any of the above embodiments, wherein the housing 100 includes the polymer ceramic layer 10. Referring to fig. 4, a schematic structural diagram of a housing 100 according to an embodiment of the present disclosure is shown, in which the housing 100 includes a polymer ceramic layer 10. The shell 100 provided by the application has the advantages of high surface hardness, good strength, good ceramic texture and wide application prospect.
In the present embodiment, the polymer ceramic layer 10 includes polymer and ceramic particles. In one embodiment, the polymer in the polymer ceramic layer 10 is crosslinked into a three-dimensional network structure, and the ceramic particles are dispersed in the three-dimensional network structure. In an embodiment of the present application, the polymer comprises a thermoplastic resin comprising at least one of polyphenylene sulfide, polyphenylene sulfone, polyamide, and ethylene vinyl acetate.
In the present embodiment, the mass content of the ceramic particles in the polymer ceramic layer 10 is 40% or more. The polymer ceramic layer 10 contains a large amount of ceramic particles, which can improve the surface hardness and the texture of the ceramic. Further, the mass content of the ceramic particles in the polymer ceramic layer 10 is 40% to 80%. Specifically, the mass content of the ceramic particles in the polymer ceramic layer 10 may be, but is not limited to, 40%, 45%, 50%, 58%, 60%, 65%, 72%, 75%, 80%, or the like. In an embodiment of the present application, the ceramic particles include at least one of zinc oxide, zirconium oxide, aluminum oxide, silicon dioxide, titanium oxide, and silicon carbide. The ceramic particles are high temperature resistant, corrosion resistant, high in hardness and good in strength, and are beneficial to improving the performance of the shell 100.
The hardness of the surface of the polymer ceramic layer 10 is measured under 1kg pressure by using the GB/T6739-1996 standard. In the present embodiment, the pencil hardness of the surface of the polymer ceramic layer 10 is 3H or more. Further, the pencil hardness of the surface of the polymer ceramic layer 10 is 3H-7H, so that the hardness and the strength of the shell 100 are greatly improved. Further, the pencil hardness of the surface of the polymer ceramic layer 10 is 4H to 7H. Specifically, the pencil hardness of the surface of the polymer ceramic layer 10 may be, but is not limited to, 3H, 4H, 5H, 6H, 7H, or the like.
The Vickers hardness of the polymer ceramic layer 10 is detected under the pressure of 1kg by adopting the GB/T16534-2009 standard. In the present embodiment, the vickers hardness of the polymer ceramic layer 10 is greater than or equal to 400HV. Further, the polymer ceramic layer 10 has a Vickers hardness of 400HV to 800HV. Further, the polymer ceramic layer 10 has a Vickers hardness of 500HV to 700HV. Specifically, the vickers hardness of the polymer ceramic layer 10 may be, but is not limited to, 400HV, 450HV, 500HV, 550HV, 600HV, 700HV, or 800HV, etc.
In the present application, the falling ball impact performance test is used to test the performance of the polymer ceramic layer 10, wherein the falling ball is a 32g stainless steel ball, and the thickness of the polymer ceramic layer 10 is 0.8mm. In one embodiment, the polymer ceramic layer 10 is supported on the fixture, wherein the polymer ceramic layer 10 has a support of 5mm at the periphery and a suspended middle part; and (3) freely dropping a 32g stainless steel ball from a certain height to a point to be detected on the surface of the polymer ceramic layer 10 to be detected, and recording the height of the broken polymer ceramic layer 10 as the ball dropping height. Further, a 32g stainless steel ball is freely dropped to the center of the surface of the polymer ceramic layer 10 to be tested from a certain height, each height is tested for 5 times, and the height for breaking the polymer ceramic layer 10 is recorded as the ball drop height. In the present embodiment, the polymer ceramic layer 10 has a ball drop height of 70cm or more. Further, the polymer ceramic layer 10 has a ball falling height of 70cm to 100cm. Further, the polymer ceramic layer 10 has a ball drop height of 80cm to 95cm. The polymer ceramic layer 10 has excellent drop resistance and strong toughness.
The four-point bending strength of the polymer ceramic layer 10 is detected by adopting the GB/T6569-2006 standard. In the present embodiment, the four-point bending strength of the polymer ceramic layer 10 is greater than or equal to 400N. Further, the four-point bending strength of the polymer ceramic layer 10 is 400N-800N. Further, the polymer ceramic layer 10 has a Vickers hardness of 500N to 750N. Specifically, the four-point bending strength of the polymer ceramic layer 10 may be, but is not limited to, 400N, 450N, 500N, 600N, 650N, 700N, 750N, or the like.
In the present application, the polymer ceramic layer 10 is placed on an extrusion jig, the top end of a spherical compressive head with a diameter of 10mm is aligned with the middle position of the polymer ceramic layer 10, the polymer ceramic layer 10 is pressed at a compression speed of 5mm/min until the polymer ceramic layer 10 is broken, and the peak pressure value at this time is recorded as the extrusion force. In the embodiment of the present application, the pressing force of the polymer ceramic layer 10 is greater than or equal to 500N. Further, the pressing force of the polymer ceramic layer 10 is 500N to 700N. Further, the pressing force of the polymer ceramic layer 10 is 550N-650N. Specifically, the pressing force of the polymer ceramic layer 10 may be, but is not limited to, 500N, 550N, 570N, 600N, 650N, 680N, 700N, or the like.
In the present embodiment, the polymer ceramic layer 10 may further include a colorant, so that the housing 100 has a different color appearance, thereby improving the visual effect. Specifically, the colorant may be, but is not limited to, at least one selected from carbon black, iron oxide, cobalt oxide, cerium oxide, nickel oxide, bismuth oxide, zinc oxide, manganese oxide, chromium oxide, copper oxide, vanadium oxide, and tin oxide, respectively. In one embodiment, the mass content of the colorant in the polymer ceramic layer 10 is less than or equal to 15%, so that the color of the polymer ceramic layer 10 can be improved without affecting the content of the ceramic particles. Further, the mass content of the colorant in the polymer ceramic layer 10 is 0.5% -10%.
Referring to fig. 5, which is a schematic structural diagram of a housing according to another embodiment of the present disclosure, the housing 100 may further include a protective layer 20, and the protective layer 20 is disposed on the surface of the polymer ceramic layer 10. The housing 100 has an inner surface and an outer surface opposite to each other during use, and the protective layer 20 is disposed on the outer surface side to protect the housing 100 during use. Specifically, the protective layer 20 may be, but is not limited to, an anti-fingerprint layer, a hardened layer, and the like. Specifically, the thickness of the protective layer 20 may be, but is not limited to, 0.5 μm to 3 μm. In one embodiment, the protective layer 20 comprises an anti-fingerprint layer. Optionally, the anti-fingerprint layer has a contact angle greater than 105 °. The contact angle is an important parameter for measuring the wettability of the liquid on the surface of the material, and the contact angle of the anti-fingerprint layer is larger than 105 degrees, which shows that the liquid can easily move on the anti-fingerprint layer, thereby avoiding the pollution on the surface of the anti-fingerprint layer and having excellent anti-fingerprint performance. Optionally, the anti-fingerprint layer comprises a fluorine-containing compound. Specifically, the fluorine-containing compound may be, but not limited to, a fluorosilicone polymer, perfluoropolyether, fluoroacrylate, and the like. Further, the anti-fingerprint layer also comprises silicon dioxide, and the friction resistance of the anti-fingerprint layer is further improved by adding the silicon dioxide. In another embodiment, the protective layer 20 comprises a hardened layer. The surface hardness and scratch resistance of the case 100 are further improved by providing the hardened layer. Optionally, the material of the hardened layer includes at least one of graphite, alumina, zirconia, silica, chromium nitride, and titanium nitride.
In the present application, the thickness of the housing 100 may be selected according to the requirements of the application scenario, which is not limited herein; in one embodiment, the housing 100 may be used as a casing, a middle frame, a decoration, etc. of the electronic device 200, such as a casing of a mobile phone, a tablet computer, a notebook computer, a watch, an MP3, an MP4, a GPS navigator, a digital camera, etc. The housing 100 in the embodiment of the present application may have a 2D structure, a 2.5D structure, a 3D structure, and the like, which may be specifically selected as needed. In one embodiment, when the housing 100 is used as a mobile phone rear cover, the thickness of the housing 100 is 0.5mm to 1.2mm. Specifically, the thickness of the housing 100 may be, but is not limited to, 0.6mm, 0.7mm, 0.8mm, 0.9mm, 1mm, 1.1mm, or 1.2mm. In another embodiment, when the casing 100 is used as a mobile phone rear cover, the casing 100 includes a main body and an extension portion disposed at an edge of the main body, and the extension portion is bent toward the main body; at this time, the housing 100 is curved.
In the present embodiment, the surface roughness of the case 100 is less than 0.1 μm. By providing the housing 100 with small surface roughness, the ceramic texture of the housing can be enhanced, and the visual effect can be improved. Further, the surface roughness of the case 100 is 0.02 μm to 0.08 μm. In the embodiments of the present application, the caseThe density of the body 100 is less than or equal to 2.6g/cm 3 . Further, the density of the case 100 is 2.3g/cm 3 -2.6g/cm 3 . The application provides a casing 100 density is little, is favorable to satisfying the development demand of frivolousization.
The following provides further explanation of the method for manufacturing the housing and the performance of the housing obtained by the method of the present application through specific examples and comparative examples.
Example 1
A method of making a housing comprising:
mixing spherical zinc oxide with the grain size of 100nm-150nm and spherical aluminum oxide with the grain size of 100-200nm according to the mass ratio of 10; mixing 20kg of composite ceramic particles, a silane coupling agent accounting for 1% of the mass of the composite ceramic particles, polyvinyl alcohol accounting for 0.5% of the mass of the composite ceramic particles and carbon black accounting for 2% of the mass of the composite ceramic particles to obtain a mixed material; adding water and alumina grinding beads into the mixed material, wherein the mass ratio of the mixed material to the water to the ball grinding beads is 1. And carrying out spray drying granulation on the mixed slurry to obtain the treated ceramic particles, wherein the feeding temperature is 80 ℃, the air inlet temperature is 150 ℃, the air exhaust temperature is 80 ℃, the temperature in the tower is 85 ℃, and the negative pressure in the tower is 100pa. Mixing the treated ceramic particles and the polymer according to a mass ratio of 8:2 mixing to form a mixture, the polymer comprising polyphenylene sulfide and polyphenylene sulfone; the mixture was placed in a blending extruder, blended 3 times, and then extruded for pelletization to obtain an injection-molded feed. Drying the injection molding feed at 120 ℃ for 12h, and then adding the injection molding feed into an injection machine for injection molding; the molding temperature is 345 ℃, the injection speed is 90%, the injection pressure is 200MPa, the mold temperature is 145 ℃, and the pressure maintaining time is 30s, so as to prepare the polymer ceramic blank.
Mixing melamine and zinc according to a mass ratio of 6. And uniformly coating the pretreatment liquid on a polymer ceramic blank in a coating mode, and drying at 80 ℃ to form a pretreatment layer to obtain a composite blank.
Placing the composite blank into a jig, and then placing the jig and the composite blank into an oven to carry out heat treatment according to the following curve: heating the mixture to 250 ℃ at room temperature for 1h, and keeping the temperature at 250 ℃ for 1h; raising the temperature from 250 ℃ to 330 ℃ for 1h, preserving the heat at 330 ℃ for 2h, and then naturally cooling to obtain a first green body. And (3) putting the first green body into a hot-pressing sintering furnace for hot pressing, wherein the hot pressing temperature is 360 ℃, the heat preservation time is 4 hours, the hot pressing pressure is 40MPa, the hot pressing atmosphere is nitrogen, and naturally cooling after the hot pressing is finished to obtain a second green body.
CNC machining is carried out on the second blank according to a product drawing, a PCD milling cutter is selected for CNC machining, the rotating speed of a main shaft is 22000rpm, and the single cutting amount is 50 micrometers; then, rough polishing is carried out by a polishing machine, a polishing disc is made of pig hair matched with a buffing composite material, rough polishing liquid is water-based diamond polishing liquid, the granularity of diamond micro powder in the rough polishing liquid is 2 mu m, and the concentration of the rough polishing liquid is 10wt%; and after rough polishing, performing fine polishing by using a polishing machine, wherein the granularity of silicon oxide in the fine polishing liquid is 200nm, and the concentration of the fine polishing liquid is 40wt%, so that a pretreatment layer is removed, a polymer ceramic layer is obtained, and the shell is prepared.
Example 2
The difference from example 1 is that after the polymer ceramic layer is prepared, a hardened layer is plated on the surface of the polymer ceramic layer by means of evaporation plating, the material of the hardened layer is alumina, the thickness of the hardened layer is 1 μm, and then the anti-fingerprint layer is plated on the surface of the hardened layer to prepare the shell.
Comparative example 1
A zirconia ceramic shell is formed by sintering a zirconia ceramic blank.
Comparative example 2
The shell was prepared according to the method shown in example 1 of patent CN 108483991A.
Comparative example 3
Substantially the same as in example 1, except that the spray coating of the pretreatment liquid was not performed, the polymer ceramic body was directly subjected to the heat treatment.
Comparative example 4
Substantially the same as in comparative example 3, except that the heat treatment process comprised heating to 250 ℃ at room temperature for 1 hour, and holding at 250 ℃ for 24 hours; the temperature is raised from 250 ℃ to 330 ℃ for 1h, and the temperature is kept at 330 ℃ for 24h.
Performance detection
The cases obtained in examples and comparative examples were subjected to tests of pencil hardness, vickers hardness, ball drop height, four-point bending strength, pressing force, and density according to the test methods described in the specification, and the results are shown in table 1, in which the thicknesses of the cases obtained in examples and comparative examples were kept uniform in each test.
TABLE 1 Performance test results
The pencil hardness and the vickers hardness of the shell are high, the shell has excellent scratch resistance, meanwhile, the falling ball height is high, the four-point bending strength is high, the extrusion force is strong, the shell has excellent toughness and strength, and the overall density is low. Compared with comparative example 1, the overall toughness of the shell provided by the embodiment of the application is improved, and the density is reduced; compared with comparative examples 2-4, the surface hardness and the overall strength of the shell provided by the embodiment of the application are greatly improved, and the application of the shell is facilitated.
The present application further provides an electronic device 200 including the housing 100 in any of the above embodiments. It is understood that the electronic device 200 may be, but is not limited to, a mobile phone, a tablet computer, a notebook computer, a watch, an MP3, an MP4, a GPS navigator, a digital camera, etc. Please refer to fig. 6, which is a schematic structural diagram of an electronic device according to an embodiment of the present disclosure, wherein the electronic device 200 includes a housing 100. The housing 100 can improve the strength and the surface hardness of the electronic device 200, and the electronic device 200 has an appearance with a ceramic texture and excellent product competitiveness. Referring to fig. 7, which is a schematic structural diagram of an electronic device according to an embodiment of the present disclosure, a structure of the electronic device 200 may include an RF circuit 210, a memory 220, an input unit 230, a display unit 240, a sensor 250, an audio circuit 260, a WiFi module 270, a processor 280, a power supply 290, and the like. The RF circuit 210, the memory 220, the input unit 230, the display unit 240, the sensor 250, the audio circuit 260, and the WiFi module 270 are respectively connected to the processor 280; the power supply 290 is used to supply power to the entire electronic device 200. Specifically, the RF circuit 210 is used for transmitting and receiving signals; the memory 220 is used for storing data instruction information; the input unit 230 is used for inputting information, and may specifically include a touch panel and other input devices such as operation keys; the display unit 240 may include a display screen or the like; the sensor 250 includes an infrared sensor, a laser sensor, etc. for detecting a user approach signal, a distance signal, etc.; the speaker 261 and the microphone 262 are connected with the processor 280 through the audio circuit 260, and are used for receiving and transmitting sound signals; the WiFi module 270 is configured to receive and transmit WiFi signals; the processor 280 is used for processing data information of the electronic device 200.
The foregoing detailed description has provided for the purposes of providing a thorough understanding of the present embodiments, and has illustrated and described the principles and embodiments of the present application, but it is to be understood that this disclosure is only illustrative of the methods and their core concepts; meanwhile, for a person skilled in the art, according to the idea of the present application, the specific embodiments and the application range may be changed. In view of the above, the description should not be taken as limiting the application.